2012
DOI: 10.1016/j.epsl.2012.06.009
|View full text |Cite
|
Sign up to set email alerts
|

A boundary exchange influence on deglacial neodymium isotope records from the deep western Indian Ocean

Abstract: The use of neodymium (Nd) isotopes to reconstruct past water mass mixing relies upon the quasi-conservative behaviour of this tracer,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 70 publications
3
37
0
1
Order By: Relevance
“…Therefore, preferential contribution from a single mineral phase within the lithogenic component is possible. Preferential contribution is consistent with laboratory leaching experiments in which the ε Nd obtained was dependent on the fraction of the particles reacting with the leach solution (Wilson et al, 2012(Wilson et al, , 2013.…”
Section: Constraints On Pore Fluid ε Ndsupporting
confidence: 77%
See 2 more Smart Citations
“…Therefore, preferential contribution from a single mineral phase within the lithogenic component is possible. Preferential contribution is consistent with laboratory leaching experiments in which the ε Nd obtained was dependent on the fraction of the particles reacting with the leach solution (Wilson et al, 2012(Wilson et al, , 2013.…”
Section: Constraints On Pore Fluid ε Ndsupporting
confidence: 77%
“…Currently, the proposal of a trace mineral preferentially dominating the particulate-fluid interaction is consistent with observations in the modern ocean and in the laboratory (e.g. Jeandel and Oelkers, 2015;Pearce et al, 2013;Rousseau et al, 2015;Wilson et al, 2012Wilson et al, , 2013. Evidence for this radiogenic trace mineral exists in bottom water from HH200.…”
Section: Cryptic Trace Mineralmentioning
confidence: 62%
See 1 more Smart Citation
“…Batch experiments or sequential leaching slightly illuminated the processes by confirming that a fraction of the lithogenic material can be dissolved, releasing some of the elements it contains and contributing to balance their isotopic composition [29][30][31][32]51]. These experiments also showed that secondary phases are rapidly formed, scavenging a large part of most of the released species.…”
Section: (D) What Do the Models Tell Us?mentioning
confidence: 70%
“…[5] For the interpretation of variations in Nd as changes in overturning circulation it is important to be able to disentangle variations resulting from changes in Nd sources from variations that are due to changes in overturning circulation [e.g., Wilson et al, 2012]. This in turn requires a good overall knowledge of the nature and magnitude of these sources.…”
Section: Introductionmentioning
confidence: 99%